Prevalence and variation of sesamoid bones in the hand: a multi-center radiographic study - Chen, Wei (Int J Clin Exp Med, 2015)
There is rare studies with regard to sesamoid bone variations of the hand in addition to its prevalence and distribution. This study aims to assess both the prevalence and variation of sesamoid bones of the hand. A retrospective review of posteroanterior (PA) and oblique radiographs of 436 left and 414 right hands of 850 adult patients obtained from four hospitals was performed. All X-ray films were examined independently for existing sesamoid bones. The presence of sesamoid bones was confirmed if oblique views revealed a small oval bone volar to the metacarpophalangeal (MCP) joint or interphalangeal (IP) joint of the thumb or finger. The X-ray films consistently revealed two sesamoid bones at the MCP joint of the thumb, and 30.4% were identified with variation, which can be classified into three distinct types based upon the number of ossification centers and the shape of fusion lines seen on standard PA and oblique films. The prevalence of sesamoid bones was 60.8% for index finger MCP joint and 59.1% for small finger MCP joint. At the thumb IP joints, sesamoid bones were only seen in 15.9% hands. Two sesamoid bones were rarely seen in other joints of the hand except thumb MCP joints.